DAMPAK KONSERVATISME AKUNTANSI, UKURAN PERUSAHAAN PADA KUALITAS LABA DIMODERASI OLEH KOMISARIS INDEPENDEN - Lusiana Lusiana; Rini Tri Hastuti (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
This review aims to examine what accounting conservatism and firm size mean toearnings quality and the effect of independent commissioners on the correlationbetween accounting conservatism with firm size and earnings quality in manufacturingcompanies listed on the Indonesia Stock Exchange in 2018-2020. The tests in thisreview were carried out using a purposive testing strategy in which information wasobtained from 51 organizations during 2018 to 2020. Likewise, the information in thisreview was handled using the EViews 11 programming variant. The results obtainedfrom the tests carried out indicated that accounting conservatism had no significantimpact on earnings quality. While the size has a significant effect on the quality ofincome. Then, at that time, the independent commissioner who acted as a moderatingvariable was able to moderate the relationship between accounting conservatism andearnings quality but could not moderate the relationship between firm size and earningsquality.